A study of a conductive laminar jet flow in an applied magnetic field. (October 2019) - Hsu, Cheng-Hsing; Tsai, Te-Hui; Chang, Ching-Chuan; Chen, Yi
This study investigates steady two-dimensional laminar confined jet flow in the presence of an applied magnetic field. The magnetohydrodynamic equations with the format of the stream function and vorticity formulation of the fluid flow are solved numerically. A numerical method was developed by using a first-order upwind scheme at the boundaries and a second-order finite control volume scheme in the flow field. The results show that the expansion region of the jet is moving downstream while the channel width and the Reynolds number are increasing. The vortex and the recirculation zone are stretched with increased Hartmann number, and the jet expansion region is moving upstream while the vortex and the recirculation zone are reduced. The channel width and the Reynolds number for the jet development are positive efforts and the Hartmann number has a suppressed effect in the present confined jet flow field.